2012
DOI: 10.1038/gene.2012.49
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome characterization of immune suppression from battlefield-like stress

Abstract: Transcriptome alterations of leukocytes from soldiers who underwent 8 weeks of Army Ranger training (RASP, Ranger Assessment and Selection Program) were analyzed to evaluate impacts of battlefield-like stress on the immune response. About 1400 transcripts were differentially expressed between pre- and post-RASP leukocytes. Upon functional analysis, immune response was the most enriched biological process, and most of the transcripts associated with the immune response were downregulated. Microbial pattern reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In humans, it has also been reported that soldiers undergoing a battlefield-like stress program demonstrated an increase in hsa-miR-155 levels in leukocytes exposed to SEB ex vivo (32), indicating that stress-related inflammation could also potentially lead to the increase in miR-155. The current study further suggests that the acute inflammatory response in the lungs to a bacterial superantigen is also regulated by miR-155, inasmuch as SEB-exposed miR-155 Ϫ/Ϫ mice having fewer infiltrating T cells than their WT counterparts and almost normal lung histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it has also been reported that soldiers undergoing a battlefield-like stress program demonstrated an increase in hsa-miR-155 levels in leukocytes exposed to SEB ex vivo (32), indicating that stress-related inflammation could also potentially lead to the increase in miR-155. The current study further suggests that the acute inflammatory response in the lungs to a bacterial superantigen is also regulated by miR-155, inasmuch as SEB-exposed miR-155 Ϫ/Ϫ mice having fewer infiltrating T cells than their WT counterparts and almost normal lung histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…1 But complete and differential counts of post-RASP white blood cells (WBCs) are within normal ranges. 1 The compromised protective immunity and impaired response to the in vitro SEB challenge in spite of normal ranges of cell counts were considered to be indicators of the anergic state of post-RASP leukocytes to SEB. 1 The SEB toxin is a category B select agent 2 and a potent mitogen 3 with affinity to polymorphic major histocompatibility complex class II molecules with potential to stimulate different clones of T-cells.…”
Section: Introductionmentioning
confidence: 97%
“…1 Transcript mediators of compromised immunity remained suppressed in post-RASP leukocytes that are ex vivo exposed to Staphylococcal enterotoxin B (SEB). 1 But complete and differential counts of post-RASP white blood cells (WBCs) are within normal ranges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein kinase C (PKC) activators like phorbol esters and Bryostatins affect the signal transduction pathway, which has enormous effect on a variety of biological responses, which include proliferation and differentiation (Cambier and Ransom, 1987;King, 1988;Isakov et al, 1986;Muhie et al, 2013). Bryostatins are antipromoters of tumour cells (Hennings et al, 1990); hence they are more significant in clinical trials, than phorbol esters like phorbol myristate acetate (PMA), which are carcinogenic (Nishimoto et al, 2013;Hennings et al, 1987).…”
Section: Introductionmentioning
confidence: 99%